PENGARUH DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP TOTAL QUALITY MANAGEMENT (TQM) PADA PDAM TIRTA RAJA KAB. OKU - Devia Amanda; Dahlia .; M. Apriliansyah. R (Ekonomika, 2024)
This research aimed to determine the influence of work discipline and work commitment on total quality management (TQM) at the Tirtaraja Regional Drinking Water Company (PDAM), OKU Regency. The data collection technique in this research was through distributing questionnaires with a population of 151 people and a sample of 60 people. The data analysis technique used was Multiple Linear Regression. Based on the partial analysis results, there was an influence of the Work Discipline variable (X1) on Total Quality Management (Y) with a tcount of 4.905 >ttable 2.002, there was an influence of the Work Commitment variable (X2) on Total Quality Management (Y) with a tcount of 5.083 >ttable 2.002, simultaneously it was found that there was an influence of Work Discipline and Work Commitment on Total Quality Management (TQM) with a calculated F value of 41.875 >Ftable 3.16. The coefficient of determination (R Square) obtained was 0.595, this showed that 59.5% of the contribution from Total Quality Management (TQM) at the Regional Drinking Water Company (PDAM) Tirtaraja OKU Regency could be explained by the variables Work Discipline (X1) and Work Commitment (X2) while the remaining 40.5% was influenced by other variables apart from those in this research, for example Leadership, Rewards, Environment, etc. (Afandi, 2018:20)